A RISING KURDISH SEPARATIST MOVEMENT IN IRAN AS PROTECTED SOCIAL CONFLICT BETWEEN IRANIAN GOVERNMENT AND KURDISH (CASE STUDY: PARTIYA JIYANA AZAD E KURDISTANE (PJAK) IN 2004) - Hafitz Setiawan (HI 15 UMY 205, 2015)
*205 Kurds, internationally, is recognized as one of ethnics in Middle East who has been living for a long time with their nomadic lifestyle. Kurdistan itself came as the dream of independent land for all Kurds. Unfortunately, this concept was only an imagination. Their struggle into their dream was faced by the failures since the beginning of their movements in 20th century. Turkey, Iran, Iraq, and Syria are places for them to live now and those governments have already become the subject of Kurdish struggle. During World War I and II, Kurdish elites and Aga tried to consolidate their movement by establishing Kurdish parties.